Microbiological, pathological and microelement analyses in vicuñas affected with "dandruff" - Rosadio A., Raúl (2012)
In recent years important economic losses have resulted from what is described as “dandruff” in vicuña fiber. With the goal of analyzing the possible cause/s was conducted an histopathological analysis of 75 skin biopsies (33 affected/42 unaffected), microbiological analysis of 85 skin/fiber scrapings (44 affected/41 unaffected), and microelement analysis (zinc, selenium, copper, molybdenum) of 70 serum samples (41 affected/ 29 unaffected), collected from three wild populations in the communities of Huaytará, Ayaví and Santa Rosa de Tambo, Huancavelica, Peru, as well as from the captive herd held jointly by these communities. The affected vicuñas were clinically normal and the presence of “dandruff” was generally detected after shearing. In these fleeces, white scales scattered or accumulated and firmly adhered to the fibers were found, especially on the flanks and backs of the animals, but also widely dispersed throughout the fleece. Histopathological analysis of the skin biopsies revealed that both affected and unaffected animals had moderate to severe dermatosis (hyperkeratosis – orthokeratosis), with moderate to severe atrophy of the inner root sheath of the follicle, but without evidence of inflammation. Microbiological analysis determined the presence of fungus species in 63.3% (28/44) of the affected and 41.5% (17/41) of unaffected animals, including Ulocladium spp., Penicillum spp., Hialofomicetos, Geotrichum candidum and Aspergilus flavus. Microelement analysis revealed 10 fold selenium concentration as compared to normal values, especially in the captive population (affected: 3.23 ± 1.31 μg/ mL; unaffected: 3.56 ± 2.27 μg/mL) possibly due to overgrazing of pastures with presence of Astragalus spp., a common seleniferous plant in the region. All animals showed cooper deficiency. Also, all animals from Santa Rosa de Tambo and affected animals from Huaytará were zinc deficient.